Real-life patterns of use and effectiveness of bortezomib: the VESUVE cohort study. Issue 4 (April 2014) - Fourrier-Réglat, Annie; Noize, Pernelle; Facon, Thierry; Fermand, Jean-Paul; Fitoussi, Olivier; Marit, Gérald; Thomaré, Patrick; Robinson, Philip; Bignon, Emmanuelle; Jové, Jérémy; Lassalle, Régis; Rouyer, Magali; et al.
Abstract In response to a regulatory request for real-life data on patterns of use and survival outcomes, 793 patients initiating bortezomib for multiple myeloma in France (May 2004–April 2006) were included in this observational study. Data were collected from medical files and patients were followed for 2 years, with vital status collected after 3 years. In total 779 patients were analyzed: 83.1% had immunoglobulin G (IgG) or IgA M-component, mean age was 65.7 years and 46.5% were female. Bortezomib was initiated as third-or-later line in 82.0%. For 75.9%, the starting dose was 1.3 mg/m2; 42.6% had bortezomib alone, 54.0% with dexamethasone. The mean number of bortezomib cycles was 5.0. Three-year overall survival from bortezomib initiation was 31.4% (95% confidence interval, CI [28.1; 34.7]) and median overall survival was 19.6 months. Two-year progression-free survival was 12.0% (95% CI [9.8; 14.4]), and median progression-free survival was 7.2 months. Overall best response was 44.0%. Survival outcomes during real-life use of bortezomib were within the range of those reported in clinical trials.